The effects of international migration on the well-being of native populations in Europe - William Betz; Nicole B. Simpson (IZA Journal of Migration, 2013)
Very little is understood about how immigrants affect the happiness, or subjective well-being of natives. We use the European Social Survey to analyze the effects of aggregate immigration flows on the subjective well-being of native-born populations in a panel of 26 countries between 2002 and 2010. We find that recent immigrant flows have a nonlinear, yet overall positive impact on the well-being of natives, with the largest effects coming from immigrant flows arriving in the previous year. Our results are small in magnitude and in practical application; only large immigrant flows would affect native well-being significantly.
Keywords: F22; I31; O15; 330; international migration; happiness; life satisfaction